All-inorganic perovskite CsPb(Br/I)3 nanorods for optoelectronic application. Issue 33 (8th August 2016) - Tang, Xiaosheng; Zu, Zhiqiang; Shao, Haibing; Hu, Wei; Zhou, Miao; Deng, Ming; Chen, Weiwei; Zang, Zhigang; Zhu, Tao; Xue, Junmin
Abstract : The CsPb(Br/I)3 nanorods with a uniform rod shape were prepared by a facile hot-injection method, and the excellent photoresponse performance was further studied. Abstract : Halide perovskites have attracted great attention in recent years as promising materials for optoelectronic devices, especially inorganic perovskites like CsPbX3 (X = I, Br, Cl). Herein, CsPb(Br/I)3 nanorods with a photoluminescence (PL) spectrum located at 610 nm have been obtained by a facile hot-injection method, and the UV-vis absorption spectrum further revealed that the bandgap absorption is around 1.98 eV. Furthermore, the photoelectric response of the CsPb(Br/I)3 nanorods showed a relatively short rise-time (0.68 s) and decay-time (0.66 s), and the on/off photocurrent ratio of the CsPb(Br/I)3 nanorod based photodetector was up to 10 3 .